Deregulation of levels of angiopoietin-1 and angiopoietin-2 is associated with severe courses of hantavirus infection - Nußhag, Christian; Baumann, Alexandra; Schnitzler, Paul; Zeier, Martin; Krautkrämer, Ellen (Clinical and diagnostic virology, 2017)
Hantavirus disease is characterized by endothelial dysfunction. Angiopoietin-1 (Ang-1) and its antagonist angiopoietin-2 (Ang-2) play a key role in the control of capillary permeability. Ang-1 is responsible for maintenance of cell-to-cell contacts whereas Ang-2 destabilizes monolayers. An imbalance of Ang-1 and Ang-2 levels results in enhanced permeability and capillary leakage. To analyze the involvement of angiopoietins in hantavirus-induced disruption of endothelia, we measured the levels of Ang-1 and Ang-2 in hantavirus infection.